Cleavage of adenine-modified functionalized DNA by type II restriction endonucleases - Macícková-Cahová, Hana; Hocek, Michal (Nucleic acids research, 2009)
A set of 6 base-modified 2'-deoxyadenosine derivatives was incorporated to diverse DNA sequences by primer extension using Vent (exo-) polymerase and the influence of the modification on cleavage by diverse restriction endonucleases was studied. While 8-substituted (Br or methyl) adenine derivatives were well tolerated by the restriction enzymes and the corresponding sequences were cleaved, the presence of 7-substituted 7-deazaadenine in the recognition sequence resulted in blocking of cleavage by some enzymes depending on the nature and size of the 7-substituent. All sequences with modifications outside of the recognition sequence were perfectly cleaved by all the restriction enzymes. The results are useful both for protection of some sequences from cleavage and for manipulation of functionalized DNA by restriction cleavage.
Keywords: deoxyadeninnukleotidy; DNA-dependentní DNA-polymerasy; elektroforéza v polyakrylamidovém gelu; Deoxyadenine Nucleotides; Electrophoresis, Polyacrylamide Gel; štěpení DNA; Deoxyribonucleases, Type II Site-Specific; Deoxyadenosines; DNA-Directed DNA Polymerase; restrikční endonukleasy typu II; DNA; DNA Cleavage; deoxyadenosiny